QUALITY CHARACTERISTICS OF CASSIA SIEBERIANA L.SEED OIL - Warra, A. A. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2016)
Oil was extracted from the seed of Cassia sieberiana Lusing soxhlet apparatus. The oil yield was 9.26±0.01% and the colour of the seed oil was dark yellow. The results of the physico-chemical analysis revealed the following; acid value, iodine value, saponification value, peroxide value, relative density and refractive index of 0.35±0.01 mgKOH/g , 135.60 ±0.10 gI2/100g, 235.62 ±0.01 mgKOH/g, 1.8 ±0.10meq H2O2 , 0.8185±0.00 (g/cm3) and 1.4415 ±5.77 respectively indicating the suitability of the seed oil for pharmaceutical and cosmetic applications.